E-LITIGATION AS THE AMENITIES FOR THE PRINCIPLE OF CONTANTE JUSTITIE MANIFESTATION OF CIVIL JURISDICTION IN INDONESIA - Zil Aidi (JCH (Jurnal Cendekia Hukum), 2021)
E-litigation or electronic-based trials is one of the features of e-court. This study seeks to provide answers regarding the extent to which the role of e-litigation in realizing the principle of contante justitie in the judiciary in Indonesia, especially in civil courts. This research also discusses what factors hinder the implementation of e-litigation in civil courts in Indonesia. The research that uses Yogyakarta District Court (PN) and Marabahan District Court (PN) as the object is qualitative research, which is juridical empirical and analyzes the collected data using qualitative descriptive methods.) The results showed that both the Yogyakarta District Court and the Marabahan District Court had e-litigation features available. Still, they had not fully contributed optimally in realizing the contante justitie principle in civil court. In the two PN's above, there are already several court users who use the e-litigation feature, especially regarding the submission of claims, answers, replicas, duplicates, conclusions, and written evidence electronically as reading the verdict electronically. However, for the electronic examination of witness and expert evidence, no court user has used it. The things that hinder the implementation of e-litigation in those district courts are court users' reluctance to use the e-litigation feature due to the unpractical regulation and the lack of internet availability signal access.